2011
DOI: 10.3345/kjp.2011.54.8.345
|View full text |Cite
|
Sign up to set email alerts
|

2009 H1N1 influenza virus infection and necrotizing pneumonia treated with extracorporeal membrane oxygenation

Abstract: A 3-year-old girl with acute respiratory distress syndrome due to a H1N1 2009 influenza virus infection was complicated by necrotizing pneumonia was successfully treated with extracorporeal membrane oxygenation (ECMO). This is the first reported case in which a pediatric patient was rescued with ECMO during the H1N1 influenza epidemic in Korea in 2009.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…The most common diagnosis in this group was pneumonia (14 of 25), including bacterial and viral etiologies. Ji et al [ 10 ] reported successful treatment with ECMO of a 3-year-old girl with acute respiratory distress syndrome and necrotizing pneumonia from an H1N1 influenza viral infection during the 2009 H1N1 influenza epidemic. In another report, Choi et al [ 9 ] reported early success rates in pediatric patients with respiratory failure on venovenous ECMO using double-lumen cannulas.…”
Section: Discussionmentioning
confidence: 99%
“…The most common diagnosis in this group was pneumonia (14 of 25), including bacterial and viral etiologies. Ji et al [ 10 ] reported successful treatment with ECMO of a 3-year-old girl with acute respiratory distress syndrome and necrotizing pneumonia from an H1N1 influenza viral infection during the 2009 H1N1 influenza epidemic. In another report, Choi et al [ 9 ] reported early success rates in pediatric patients with respiratory failure on venovenous ECMO using double-lumen cannulas.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies are case studies most of which are about the pandemic H1N1 in 2009. Reports have shown different mortality rates of severe influenza in which ECMO was applied between 8% and 75%, but the average mortality rate was 32%, indicating a relatively good effect [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. Therefore, it is recommended to apply ECMO to an influenza patient presenting continued hypoxia which does not respond to a conventional treatment (BIII).…”
Section: Extracorporeal Membrane Oxygen-ationmentioning
confidence: 99%